Implementasi Kebijakan Badan Usaha Milik Desa (BUMDes) dalam Pengembangan Califour Ketapang - Kristanti, Widya; Sukmana, Hendra (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
BUMDes have benefits and develop the potential of the tourism sector. The development of tourism in Ketapang Village began with the establishment of BUMDes. This research aims to analyze the development policy of Califour in Ketapang Village, Sidoarjo Regency. The research method applied is descriptive type with a qualitative approach. This research focuses on determining the level of success in the BUMDes implementation process in the policy of supporting the village economy through Califour Ketapang tourism. The results of this research use the concept of Van Meter and Van Horn theory (in Agustino, 2014: 139) which consists of 6 (six) indicators, namely. First, the size and objectives of the policy can be concluded if the implementation of the Ketapang BUMDes policy is appropriate because the policy can be realized well. Second, the resources of BUMDes Ketapang in implementing the BUMDes Policy are said to be inappropriate because the process of implementing the BUMDes Policy in Ketapang, the Human Resources they have are not yet competent. Third, Communication between Organizations that the communication that BUMDes Ketapang has with parties related to the process of implementing the BUMDes Ketapang Policy in the development of Tourism Villages is said to be appropriate. Fourth, Environmental, Economic, Social and Political Conditions. The process of implementing BUMDes Policy in developing Tourism Villages through Agrotourism development does not experience any obstacles because the Social, Economic and Political Environmental conditions are supportive.